Pain Education Issues in Developing Countries and Responses to them by the International Association for the Study of Pain - Michael Bond (Pain Research and Management)
Unrelieved pain remains a global health problem. There is a major difference between what could be done to relieve pain and what is being done in developing countries – this is known as the ‘treatment gap’. Poor education of health professionals, limited facilities for pain treatment and poor access to drugs for pain relief are contributing factors. While enthusiasm for pain education and clinical training in developing countries has grown, restrictions by governments and health administrations have represented a significant barrier to practice changes. Since 2002, the International Association for the Study of Pain, through its Developing Countries Working Group, has established a series of programs that have resulted in significant improvements in pain education and the clinical management of pain, together with the beginnings of a system of pain centres. These pain centres will act as regional hubs for the future expansion of education and training in pain management in developing countries. Further success will be increased with the demolition of barriers to the treatment of people in pain worldwide.